Curriculum Content, Placement, and Alignment: From Textbooks to Education Standards and Assessments - Weldon F. Zenger; Sharon K. Zenger (Educational Considerations, 2003)
The dominant role of textbooks in curriculum planning and development as well as in content grade placement and alignment goes without question.